1972
DOI: 10.1136/jnnp.35.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of blood nerve barriers in the diabetic rat

Abstract: SUMMARY An albumin-Evans blue conjugate has been used as a fluorescent tracer to demonstrate the increased permeability of endoneurial capillaries and perineurial sheath of the sciatic nerve of the alloxan-diabetic rat. The significance of the extravasation of protein into the endoneurial space is discussed in relation to the altered dynamics of the endoneurial microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 51 publications
(41 reference statements)
4
17
0
Order By: Relevance
“…Delayed axoplasmic flow as an axonal dysfunction was detected in streptozotocin diabetes rats (Schmidt et al 1975). Excess permeability of blood-nerve barriers was also demonstrated (Seneviratne 1972).…”
Section: Discussionmentioning
confidence: 92%
“…Delayed axoplasmic flow as an axonal dysfunction was detected in streptozotocin diabetes rats (Schmidt et al 1975). Excess permeability of blood-nerve barriers was also demonstrated (Seneviratne 1972).…”
Section: Discussionmentioning
confidence: 92%
“…While, for instance, alloxan-diabetic rats showed increased permeability to macromolecules (Seneviratne, 1972), comparative reports in genetically diabetic rats, C57BI/Ks (db/db) mice and streptozotocin-diabetic rats excluded any abnormality . In particular, the occasional reduction in the development of tight junctional strands in the zonulae occludentes of C57B1/Ks (db/db) mice seems not to modify the permeability of the perineurium, at least to the largest macromolecules, such as HRP, Evans Blue and albumin (Sima & Robertson, 1978b).…”
Section: Tight Junctionsmentioning
confidence: 98%
“…Seneviratne and Peiris (1969), studying the effect of hypoxia on isolated mammalian nerves, have demonstrated that the time taken for a conduction block to develop in hypoxia is about the same as the time taken for conduction block to occur during cuff induced ischaemia in human peripheral nerves. Further, Seneviratne andPeiris (1968a, 1969) have shown that the sequence of excitability change observed in human peripheral nerves during ischaemia is reproduced in isolated hypoxic rat sciatic nerves. The nerves pass through an initial phase of hyperexcitability which lasts from 2 to 10 minutes before being inactivated in 20 to 30 minutes.…”
mentioning
confidence: 99%
“…Fenn and Gerschmann (1950) and Shanes (1949) have reported the leakage of intracellular K' from nerve fibres during anoxia, while Shanes (1949), Huxley and Stiimpfli (1951) and Adrian (1956) have shown that an increase in the external K' concentration leads to a reduction of 502 the resting membrane potential. Seneviratne andPeiris (1969, 1970) have suggested that this depolarization of the membrane would initially produce a lowering of its threshold and finally lead to a depolarization block. For anoxia to produce such a conduction block it is not only necessary for intracellular K' to leak out, but also for this K' to be held up in a periaxonal space in close proximity to the axonal surface, for it is the resulting increase of periaxonal K' concentration that produces the conduction block.…”
mentioning
confidence: 99%
See 1 more Smart Citation